Clinical Profile of HIV/AIDS-infected Patients Admitted to a New Specialist Unit in Dhaka, Bangladesh - A Low-prevalence Country for HIV (Journal of Health, Population and Nutrition, 2011)
This paper describes the clinical features of a series of patients admitted to the specialist HIV/AIDS unit (Jagori) of the Dhaka Hospital, ICDDR,B (International Centre for Diarrhoeal Disease Research, Bangladesh) during May 2008–February 2010. Data were collected from a review of documents and electronic case-records and collation of laboratory results with respect to CD4 counts. One hundred and nine patients were admitted during this period. Their mean age was 33.4 years, and 62% were male. On admission, the mean CD4 count±standard deviation (SD) was 244±245 (range 2-1,549). The death rate was 12%. The patients were classified as World Health Organization clinical stage 1: 23%, stage 2: 30%, stage 3: 23%, and stage 4: 24% during the admission. The commonest diagnosis recorded was tuberculosis (TB) (23%), which was also the commonest cause of death (38%). Even for those clinicians with limited experience of managing AIDS cases, the commonest problem encountered in this patient group was TB, reflecting the continued high burden of TB on health services in Bangladesh. Additional challenges to managing TB/HIV co-infection include atypical presentations in HIV-infected persons and the complex drug interaction with antiretroviral therapy. Key words: Acquired immunodeficiency syndrome; HIV; Tuberculosis; Retrospective studies; Bangladesh. DOI: 10.3329/jhpn.v29i1.7562 J HEALTH POPUL NUTR 2011 Feb;29(1):14-19